-(8+12k)=-2(8k-4)

Simple and best practice solution for -(8+12k)=-2(8k-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8+12k)=-2(8k-4) equation:


Simplifying
-1(8 + 12k) = -2(8k + -4)
(8 * -1 + 12k * -1) = -2(8k + -4)
(-8 + -12k) = -2(8k + -4)

Reorder the terms:
-8 + -12k = -2(-4 + 8k)
-8 + -12k = (-4 * -2 + 8k * -2)
-8 + -12k = (8 + -16k)

Solving
-8 + -12k = 8 + -16k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '16k' to each side of the equation.
-8 + -12k + 16k = 8 + -16k + 16k

Combine like terms: -12k + 16k = 4k
-8 + 4k = 8 + -16k + 16k

Combine like terms: -16k + 16k = 0
-8 + 4k = 8 + 0
-8 + 4k = 8

Add '8' to each side of the equation.
-8 + 8 + 4k = 8 + 8

Combine like terms: -8 + 8 = 0
0 + 4k = 8 + 8
4k = 8 + 8

Combine like terms: 8 + 8 = 16
4k = 16

Divide each side by '4'.
k = 4

Simplifying
k = 4

See similar equations:

| 3(2x+6)+12= | | 10-w+6w-22= | | (4r^3+3r^4)-(r^4-5r^3)= | | 15x+20x+5x+5=180 | | 20-5x=x+26 | | a+9=9 | | (3a^2+1)-(4+2a^2)= | | 24=y-10 | | 1-y=12 | | 3(2x+4)=-16 | | 9x-5=-3x+6 | | r-18=12 | | 4+11(10+13x)=13x-2(x+9) | | (4+2n^3)+(5n^3+2)= | | -2+5=-4 | | -6x-2=9x^2+1 | | -14(p+1)+4(p-7)=-3p-p | | 6-x+12= | | 5x^2-13x-0=0 | | -5u+4+8u=48 | | 10(1-3v)=-8(6v+1) | | 6x^2-12x=48 | | 49x^2-28+4=0 | | 14=12-8m+66 | | 3x^2=-16x+12 | | 4n^2+12n+9=0 | | -4x-5=-8 | | 4(k-5)=-40 | | 5.9+1.8n=1.94 | | 4t+(3+5t)(4t)=x | | 209=16x^2-32x-15 | | 10x+3=9x+9 |

Equations solver categories